Challenges of Indonesian Defense Resilience in the Face of Contemporary Technology Advancement: What’s Next? - Mirza Mahbub Wijaya; Naswa Bayu Tsabita; Fathan Mubina Dewadi (Badan Pembinaan Ideologi Pancasila, 2024)
This article discusses the concept of national resilience in the digital era, which extends beyond the paradigm of conventional warfare to address a wide range of challenges. To develop the concept of national resilience ideology, a conceptual research method with a philosophical approach is employed, supported by data triangulation using Miles and Huberman's method. The main findings highlight the importance of digital security and privacy, as well as the role of digital local wisdom in strengthening national identity. Additionally, increased legal awareness is considered crucial in shaping cultural norms, while the sustainable development of human resources, supported by quality education and healthcare services, remains a key focus